Proceedings of the 23rd International Conference on World Wide Web 2014
DOI: 10.1145/2567948.2576945
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the user-generated content (UGC) uploading behavior on youtube

Abstract: YouTube is the world's largest video sharing platform where both professional and non-professional users participate in creating, uploading, and viewing content. In this work, we analyze content in the music category created by the nonprofessionals, which we refer to as user-generated content (UGCs). Non-professional users frequently upload content (UGCs) that are parodies, remakes, or covers of the music videos uploaded by professionals, namely the official record labels. Along with the success of official mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…YouTube is used every day by millions of individuals to share various kinds of videos, e.g., music, lectures, gaming, video blogs, etc. [60]. Organized groups are also active on the platform; some use it to reach and grow their network of support and organize activities, while others to propel radicalization and initiatives against other groups.…”
Section: Related Workmentioning
confidence: 99%
“…YouTube is used every day by millions of individuals to share various kinds of videos, e.g., music, lectures, gaming, video blogs, etc. [60]. Organized groups are also active on the platform; some use it to reach and grow their network of support and organize activities, while others to propel radicalization and initiatives against other groups.…”
Section: Related Workmentioning
confidence: 99%
“…User-generated-content (UGC) websites [1,2,3] refer to those whose contents rely on users' post. In the last decades, we have witnessed an increasing number of UGC websites such as videosharing website YouTube, question-and-answers website Quora and online encyclopedia Wikipedia where users generate contents autonomously.…”
Section: Introductionmentioning
confidence: 99%
“…A typical scenario is that after official K-pop music videos are uploaded on YouTube by official channels of entertainment companies or record labels, a number of related UGCs such as parodies, remakes, dance, or covers start to be uploaded and circulated on YouTube. Park et al (2014) explored the music-related UGCs by identifying a variety of trending music videos, including acoustic, cover, dance, flash mob, parody, reaction, remake, and remix. Based on Park et al's categorization of music video-related UGC, and found that analyzing UGCs is important to understand the popularity of the original content.…”
Section: Types Of K-pop Ugc Videos On Youtubementioning
confidence: 99%
“…The consumption behavior of K-pop videos was operationalized as the frequency and importance of consumption of K-pop music video-related UGC, PGC (professional generated content). The classification of music video related to UGC and PCG was developed by Park et al (2014) and later adapted by Xu et al (2016). Twenty items asking about frequency and the importance of consumption of specific types of videos on 7-point Likert-type scale ranging from never to several times a day, and not at all important to very important were listed for participants to evaluate.…”
Section: The Consumption Of K-pop Videosmentioning
confidence: 99%
See 1 more Smart Citation